Bleach-Associated Uveitis: A Case Report - Gueorgui Markov; Yani Zdravkov; Alexander Oscar (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Introduction: Chemical ocular injuries represent ophthalmologic emergencies with potentially blinding complications. Burns with alkalis tend to be more serious due to deeper tissue penetration as a result of colliquative necrosis. Uveitis is usually observed in higher grades of burns with significant alterations in the anterior segment of the eye. This study aimed to report a case of late-onset unilateral uveitis following a mild alkali burns with sodium hypochlorite (bleach). Case presentation: A 64-year-old Caucasian woman reported that 3 weeks ago, she had an accident with bleach coming in contact with both eyes. At that time, she had emergency ocular irrigation with saline to both eyes, and she had also used artificial tears for about a week. Besides bilateral conjunctival hyperaemia and punctate corneal epithelial erosions, no other complications had been noted. Her symptoms had subsided in several days. Upon presentation to the clinic, reduced best-corrected visual acuity was observed in both eyes to 20/30, which was attributed to age-related cataracts, normal intraocular pressure, normal conjunctiva in both eyes, the clear cornea in the right eye (OD) and several white, round, middle-sized granulomatous keratic precipitates in the left eye (OS), without epithelial and stromal alterations. The anterior chamber of OS demonstrated a 0.5+ cellular reaction. The remaining ocular status was normal. Conclusion: Based on the history of chemical ocular injury, the lack of systemic diseases and the mild form of ocular inflammation, no additional diagnostic tests were offered. The patient was started on topical dexamethasone phosphate for 1 month with an initial dose of one drop four times daily, which led to remission.